Pengembangan Kurikulum Berbasis Nilai-Nilai Islam ‎di TK Islam Darul Arifin Jambi - Cut Citra Novita; Neti Familiani; Muhammad Fachdir Saputra; Sukiman (STAI Terpadu Yogyakarta, 2022)
Early childhood is an important asset for a country to build a civilization that must grow and develop. Curriculum based on Islamic values is used to shape children according to the guidelines of the Qur'an and Hadith. The implementation of Islamic-based PAUD refers to the optimization of religious education programs. This research was conducted at the Islamic Kindergarten Darul Arifin Jambi. This study uses a qualitative descriptive research. The method used is observation, interviews and documentation. The purpose of this study was to determine and describe the development of the 2013 Islamic-based curriculum in Islamic Kindergarten Darul Arifin Jambi, how the procedures for developing and forms of Islamic values-based curriculum learning activities in Islamic Kindergarten Darul Arifin Jambi. The results of the study indicate that the form of superior religious education programs is carried out in the form of STEAM Quran activities